Compliance with Halal Standards in Honey Production: Identification of Critical Points in Malang Region - Susilo, Agus; Masyithoh, Dewi; Prihanto, Asep Awaludin; Akhiroh, Puji; Andriani, Ria Dewi; Rahayu, Premy Puspitawati; Al Awwaly, Khotibul Umam; Jaya, Firman; Amertaningtyas, Dedes; Evanuarini, Herly (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aims to identify critical control points in honey production in Malang that affect both product quality and halal status, using a qualitative approach. Data were collected through interviews, observations, and thematic analysis. The study identified several critical points in the honey production process that influence product quality and halal certification status, namely: the source of bees, hive cleanliness, processing methods, and packaging.The findings indicate that 80% of beekeepers understand and apply halal principles, while the remaining 20% require further education. Halal certification has been shown to increase the market value of honey by 15–20%, while also enhancing consumer trust and the product’s competitiveness in both domestic and international markets. Improving production efficiency through training, modernization of equipment, and the adoption of digital marketing strategies is essential to maximizing the potential of halal honey in the region.